2021
DOI: 10.3390/diagnostics11050815
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Artificial Intelligence Analysis with Textural Metrics Extracted by Contrast-Enhanced Mammography in the Breast Lesions Classification

Abstract: The aim of the study was to estimate the diagnostic accuracy of textural features extracted by dual-energy contrast-enhanced mammography (CEM) images, by carrying out univariate and multivariate statistical analyses including artificial intelligence approaches. In total, 80 patients with known breast lesion were enrolled in this prospective study according to regulations issued by the local Institutional Review Board. All patients underwent dual-energy CEM examination in both craniocaudally (CC) and double acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…In the last decade there has been growing consensus regarding the role of breast parenchyma as an independent risk factor for breast cancer [4][5][6]: consequently, a number of approaches to breast parenchyma assessment have been proposed, among which radiomic texture feature extraction is the most spread [7][8][9]. Radiomics is an emerging field and has a keen interest, especially in the oncology field [10][11][12]: it has been shown that radiomics could be predictive of TNM grade, histological grade, response to therapy and survival in various tumors [13][14][15]. Textural radiomic features of breast parenchyma have been shown to be useful for cancer classification, too [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade there has been growing consensus regarding the role of breast parenchyma as an independent risk factor for breast cancer [4][5][6]: consequently, a number of approaches to breast parenchyma assessment have been proposed, among which radiomic texture feature extraction is the most spread [7][8][9]. Radiomics is an emerging field and has a keen interest, especially in the oncology field [10][11][12]: it has been shown that radiomics could be predictive of TNM grade, histological grade, response to therapy and survival in various tumors [13][14][15]. Textural radiomic features of breast parenchyma have been shown to be useful for cancer classification, too [16].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomic features provide data on tumor phenotype as well as cancer microenvironment. Radiomics-derived parameters, when associated with other clinical pertinent data and correlated with outcomes data, can produce accurate robust evidence-based clinical-decision support systems (CDSS) [25][26][27][28][29][30][31][32]. The possibility to connect radiological and clinical data in the present SR template could create the basis for a large database, allowing not only epidemiological statistical analyses, but also the building of radiomics models [29].…”
Section: Discussionmentioning
confidence: 99%
“…In oncology, the assessment of tissue heterogeneity is of particular interest; genomic analyses have demonstrated that the degree of tumor heterogeneity is a prognostic determinant of survival and an obstacle to cancer control. Studies have demonstrated that radiomics features are strongly correlated with heterogeneity indices at the cellular level [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, that Radiomics could support cancer detection, diagnosis, evaluation of prognosis and response to treatment, so as could supervise disease status [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though individual features may correlate with genomic data, so-called radiogenomics, or clinical outcomes, the impact of radiomics is increased when the data are processed using machine learning techniques. Nowadays, several studies have assessed the role of radiogenomics in hepatocellular carcinoma, but only a few have examined liver metastases [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%